Strategi Coping untuk Meningkatkan Subjective Well-Being Single Mother di Bali - Moniex, Ni Putu Dhita Maharani (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 1 (2020): Volume 1 Nomor 1 Tahun 2020 - Widya CakraDO - 10.24843/widyacakra.2020.v1.i1.p69191, 2020)
Grieving is one of the individual problematic situation that especially faced by Balinese woman. Grieving is not about a simple emotional, but rather a complex processes. In this situation, woman do not just lost their partner of life, but they also gain new roles and responsibilties which becoming new source of problem in their life. In Balinese tradition and regulation which is known as ‘awig-awig’, there is regulation about roles and responsibilities of a balinese woman with single mother status. The inability of a single mother to adapt in a new situation will decrease their life quality as a result of losing the subjective well being (SWB) aspects.Using coping strategy becomes an effort of a single mother to develop their SWB in order to improve their life quality. A good coping strategy namely problem focused coping and emotion-focused coping.